Fundamentals of Emulsion Polymerization - Lovell, Peter A; Schork, F. Joseph (Biomacromolecules, 2020)
A comprehensive overview of the fundamentals of emulsion polymerization and related processes is presented with the object of providing theoretical and practical understanding to researchers considering use of these methods for synthesis of polymer colloids across a wide range of applications. Hence, the overview has been written for a general scientific audience with no prior knowledge assumed. Succinct introductions are given to key topics of background science to assist the reader. Importance is placed on ensuring mechanistic understanding of these complex polymerizations and how the processes can be used to create polymer colloids that have particles with well-defined properties and morphology. Mathematical equations and associated theory are given where they enhance understanding and learning and where they are particularly useful for practical application. Practical guidance also is given for new researchers so that they can begin using the various processes effectively and in ways that avoid common mistakes.